Zambrano, Pilar & Saunders, William (eds.), Unborn human life and fundamental rights, leading constitutional cases under scrutiny, Berlin, Peter Lang GmbH, 2019, pp. 264 - Castaldi, Ligia de Jesús (2020)
Fil: Castaldi, Ligia de Jesús. Ave Maria School of Law; Estados Unidos